Geotourism attractions in intermediate destinations of peripheral regions - Vejsbjerg, Laila (2013)
This study discusses the development of palaeontologic geosites, with and without fossils remains as spaces of leisure in peripheral regions. A factor analysis was carried out on 115 geosites at natural surroundings, in 11 palaeontologic areas of North Patagonia (Provinces of Neuquen and Rio Negro, Argentina). The major research findings were four factors. 1) The exterior linkage with other attractions that makes a reference to a space of flows, 2) The distance to a populated centre that is related with the emerge of specialized segments of demand, 3) The management capacity where the role of the local community is fundamental, 4) The state-support for the setting in value of natural heritage attractions without being based on a profitability criteria. These factors contributed to understand the location of a new tourist product and the role of the secondary attractions in the incorporation of peripheral regions to the territory of tourism.